Collective patients’ rights in Polish law. Selected problems - Tykwińska-Rutkowska, Dominika (Studia Iuridica Toruniensia, 2024)
The subject of the analysis in this publication is the problem of patients’ collective rights. In an attempt to find an answer to the questions concerning the essence of these rights and the relation between legal protection against violations of these rights and the protection against violations of individual rights of patients, the analysis covers the legal solutions in the field of patients’ rights in force in Poland, as well as the related literature and administrative court decisions. In this way, it was established that Polish legislation recognises the collective rights of patients understood as the rights of actual and potential patients treated as a collective, i.e. a group that deserves special protection, and establishes an additional method of their protection by way of administration, in which the object of protection is a collective interest (proceedings on practices violating collective patients’ rights before the Patient’s Rights Ombudsman), while some legislation recognises the right to collective patient involvement.